Quantitative Analysis of Creative Thinking Skills and Concept Mastery in Physics: Temperature & Heat - Vanessa Pratiwi, Sri Mindia; Wiyono, Ketang; Ismet, Ismet; Utami , Yeni (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
This study aims to identify students' creative thinking skills and concept mastery in the context of temperature and heat material at SMA Negeri 2 Palembang and to explore the relationship between these two variables. A quantitative descriptive research design was employed, involving 60 students from class XI. Data was collected using the PhysCreTHOTS test, which assesses creative thinking and concept mastery. The results showed that students' creative thinking skills averaged 48.3%, falling within the